Constitutional Regulation of Party-Driven Recall and Democratic Accountability in Indonesia’s Parliament - Moh. Yusuf; Muliadi Muliadi; Muhammad Akbar; Abdullah Abdullah (Universitas Islam Sultan Agung, 2026)
This article critically examines party-driven recall in Indonesia’s parliamentary system, situating it within constitutional law, representation theory, and democratic accountability. The study addresses growing concerns that recall mechanisms, rather than strengthening democracy, may reinforce party control over elected representatives. It aims to analyze how recall, regulated through statutory provisions and internal party rules, affects legislative independence and the balance between party sovereignty and popular sovereignty. Using a normative legal methodology, the research combines doctrinal analysis, comparative approaches, and legal hermeneutics. Primary sources include the 1945 Constitution, relevant legislation, party constitutions, and judicial decisions, enabling an evaluation of recall within Indonesia’s asymmetric bicameral structure. The findings show that recall functions primarily as an instrument of party discipline rather than democratic accountability. Political parties use it to control legislators who deviate from party lines, thereby weakening parliamentary autonomy and shifting accountability away from constituents. This effect is intensified by the dominance of the People’s Representative Council (DPR) and the interaction between statutory and party-based rules. The study concludes that Indonesia’s recall system undermines representative democracy by prioritizing party sovereignty over voter accountability, highlighting the need for reforms aligned with democratic principles.